Characterisation of Liver Lesions on Triple Phase Computed Tomography and Studying the Social Demographics of the Liver Lesions - Anil Kumar Shukla; Javaji Ravi Prasad; Prashanth J (Asian Journal of Medical Radiological Research, 2019)
Background: To assess and characterize liver lesions using triple phase multi-detector computed tomography (MDCT) as a tool and to study the social demographics of the patients with liver lesions. Subjects and Methods: A hospital based retrospective analysis of 150 patients was done on patients with liver lesions who had undergone triple phase MDCT to characterize the liver lesions as was advised post ultrasonography or based on clinical suspicion, in a period of 3 years, from January 2015 to December 2017 in Rajarajeswari medical college and hospital and findings of triple phase MDCT were correlated with clinical/ histopathological or post-operative findings. The results were then analysed to arrive at conclusions. Results: Of the total of 150 patients with liver lesions. there were 104 benign and 46 malignant lesions. Hemangioma and metastasis were seen to be the most common lesions, with hemangioma accounting for 35 cases (24%) and metastasis 28 cases (18.6%). There were 17 cases (12%) each of abscess and simple cysts, 21 (14%) cases of hepatocellular carcinoma and 17 cases (11%) of hydatid cysts. There were 8 cases (5%) cases of focal fatty infiltration, 3 cases cases of hepatic laceration, 1% cases each of focal nodular hyperplasia, cholangiocarcinoma and hepatic contusion. Conclusion: Triphasic MDCT, owing to its strength of high speed mapping of the liver in the immediate arterial, portal venous and delayed phase assessing the enhancement pattern of lesions is an accurate and highly sensitive tool in diagnosing and characterising liver lesions.